Ottoman-Southeast Asian Relations : sources from the Ottoman Archives - Kadı, İsmail Hakkı, (Global Pentecostal and Charismatic Studies;, 2020)
Ottoman-Southeast Asian Relations: Sources from the Ottoman Archives, is a product of meticulous study of İsmail Hakkı Kadı, A.C.S. Peacock and other contributors on historical documents from the Ottoman archives. The work contains documents in Ottoman-Turkish, Malay, Arabic, French, English, Tausung, Burmese and Thai languages, each introduced by an expert in the language and history of the related country. The work contains documents hitherto unknown to historians as well as others that have been unearthed before but remained confined to the use of limited scholars who had access to the Ottoman archives. The resources published in this study show that the Ottoman Empire was an active actor within the context of Southeast Asian experience with Western colonialism. The fact that the extensive literature on this experience made limited use of Ottoman source materials indicates the crucial importance of this publication for future innovative research in the field. Contributors are: Giancarlo Casale, Annabel Teh Gallop, Rıfat Günalan, Patricia Herbert, Jana Igunma, Midori Kawashima, Abraham Sakili and Michael Talbot